ADAPTASI ALAT UKUR EMPOWERING LEADERSHIP PADA KARYAWAN GENERASI Z - Komalasari, Shanty; Handoyo, Seger; Herachwati, Nuri (Jurnal Psikologi, 2024)
Empowering leadership is a leader who can influence the potential of individuals and teams to be creative and give autonomy to organizational employees. Empowering leadership has two dimensions, namely autonomous support and developmental support. Using instruments in different cultural backgrounds requires an adaptation process so that measurement results are valid and reliable. Still, until now, there has been no research on the adaptation of empowering leadership measuring instruments in Indonesia. This study aims to obtain and test a standardized Indonesian version of empowering leadership instruments. The adaptation process uses a structural equation model (SEM). Quantitative techniques were used in this study. Data was collected through the distribution of questionnaires online. Based on the results, it can be concluded that the results of this study show evidence of validity and reliability of 0.938 with Cronbach Alpha > 0.8 criteria entering an excellent and adequate scale but can still be improved by making certain modifications so that it can be a better measuring tool when applied to look at the phenomenon of empowering in employees.